The Quality Of Life Of Informal Caregivers Of Older People With Type 2 Diabetes Mellitus In Indonesia: A Cross-Sectional Study - Rinco Siregar; Charuwan Kritpracha; Tippamas Chinnawong (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
This study aimed to assess the Quality of Life (QoL) of family caregivers of older persons with type 2 diabetes mellitus (T2DM) at home. The study utilized the 33-item Quality of Life Index to evaluate the QoL of 394 family caregivers caring for older persons with T2DM under the six Community Health Centers working area in City of Medan, Indonesia. Data analysis involved descriptive statistics and chi-square tests. The study found that the caregivers aged between 60 and 74 years reported a significantly higher prevalence of poor QoL (78.9%). Male caregivers were more likely to report poor QoL (84.7%) compared to female caregivers (45.0%). Unmarried caregivers have good QoL (100%) compared to widowed and married status (24% and 48.7%). Low level of education has poor QoL 83.1%. Spouse caregiver has poorer QoL compared to child and other relative’s relationships. Those caring for older persons with T2DM for less than 5 years (68.7% for 1-2 years and 71.9% for 3-5 years) reported poorer QoL compared to those caregiving for more than 6 years (44%). Caregivers who look after older adults with two and more than three chronic illnesses and complications tend to have a lower QoL. This study highlights that older age, male gender, married/widowed, elementary school, caregiver spouse, shorter caregiving duration (less than 5 years), and having comorbid and complication tend to have poorer QoL.